Determination of clonixin in plasma and urine by reversed-phase high-performance liquid chromatography - Bica, A (2000)
A reversed-phase high-performance liquid chromatographic method that enables the determination of clonixin in human plasma and urine samples is described. Recovery of the drug was over 87.6 and 80.7% for plasma and urine, respectively. The limit of quantitation of the method was established as 10 ng/ml in plasma and 20 ng/ml in urine samples, with RSDs of less than 11.1%. The applicability of the method was further assessed by determining the plasma concentrations time course of clonixin in six healthy volunteers after single oral dose administration of 150 and 300 mg of clonixin and Clonix,